2001
DOI: 10.1523/jneurosci.21-23-09291.2001
|View full text |Cite
|
Sign up to set email alerts
|

A Functional Role for Intra-Axonal Protein Synthesis during Axonal Regeneration from Adult Sensory Neurons

Abstract: Although intradendritic protein synthesis has been documented in adult neurons, the question of whether axons actively synthesize proteins remains controversial. Adult sensory neurons that are conditioned by axonal crush can rapidly extend processes in vitro by regulating the translation of existing mRNAs (Twiss et al., 2000). These regenerating processes contain axonal but not dendritic proteins. Here we show that these axonal processes of adult sensory neurons cultured after conditioning injury contain ribos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
351
1
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 317 publications
(372 citation statements)
references
References 89 publications
19
351
1
1
Order By: Relevance
“…Ribosomes and mRNAs have been localized to mammalian axons, suggesting at least a possible role for axonal translation (Tennyson 1970;Bassell et al 1998; Koenig et al 2000), as had been found previ-ously for dendrites (for review, see Job and Eberwine 2001). Furthermore, severed axons locally synthesize such axonal structural building blocks as neurofilaments, tubulin, and actin (Eng et al 1999;Zheng et al 2001). Intriguingly, axonal localization may be specific for axon growth-related processes-only ␤-actin mRNA is enriched in neurites and growth cones, corresponding to ␤-actin protein's localization to distal growth cones and filipodia of actively growing neurites in vitro (Bassell et al 1998) and in vivo (Weinberger et al 1996).…”
Section: Production Of the Building Blocks Both Membrane And Cytoplamentioning
confidence: 92%
See 1 more Smart Citation
“…Ribosomes and mRNAs have been localized to mammalian axons, suggesting at least a possible role for axonal translation (Tennyson 1970;Bassell et al 1998; Koenig et al 2000), as had been found previ-ously for dendrites (for review, see Job and Eberwine 2001). Furthermore, severed axons locally synthesize such axonal structural building blocks as neurofilaments, tubulin, and actin (Eng et al 1999;Zheng et al 2001). Intriguingly, axonal localization may be specific for axon growth-related processes-only ␤-actin mRNA is enriched in neurites and growth cones, corresponding to ␤-actin protein's localization to distal growth cones and filipodia of actively growing neurites in vitro (Bassell et al 1998) and in vivo (Weinberger et al 1996).…”
Section: Production Of the Building Blocks Both Membrane And Cytoplamentioning
confidence: 92%
“…In adult dorsal root ganglion (DRG) neurons in vitro, blocking axonal protein synthesis causes growth cones to retract, but only when the axons are cut off from the cell body. These experiments suggest that axonal translation is sufficient to maintain the growth cone, at least over short periods of time, but that axonal translation is not necessary if cell body-mediated protein synthesis is available (Zheng et al 2001). Embryonic Xenopus retinal axons cut off from their cell bodies can elongate and turn in vivo (Harris et al 1987) and in vitro in response to guidance cues (Campbell and Holt 2001).…”
Section: Production Of the Building Blocks Both Membrane And Cytoplamentioning
confidence: 99%
“…The reactivation of intra-axonal protein synthesis in response to nerve injury has been the first example for a role of local translation in a pathological situation [31]. Additionally, several recent reports support the idea that the axonal transcriptome and proteome are changed in amyotrophic lateral sclerosis (ALS) and spinal muscular atrophy (SMA).…”
Section: Neurodegenerative Disordersmentioning
confidence: 99%
“…During the development of the nervous system, guided axon growth requires intra-axonal mRNA translation, and it is thus not surprising that local protein synthesis is also crucial for axon regeneration. The formation of a new growth cone after axotomy of developing axons in vitro requires both local protein synthesis and degradation [30], and upon injury of mature axons, mRNAs and protein synthesis machinery are rapidly recruited into axons and intraaxonal translation is upregulated or re-activated within these mature axons [31][32][33][34]. Locally synthesized proteins are required for communication from the injured axons to their soma and likely participate in the formation of the growth bulb at the site of injury [35,36].…”
Section: Regeneration After Nerve Injurymentioning
confidence: 99%
“…There is now compelling evidence that translation occurs in axons (Koenig, 1967;Nixon, 1980;Koenig, 1991;Eng et al, 1999;Brittis et al, 2002;Piper and Holt, 2004), as mRNA and translational machinery have been localized to CNS (Tiedge et al, 1993;Aronov et al, 2001;Brittis et al, 2002), sympathetic (Olink-Coux andHollenbeck, 1996;Eng et al, 1999) and sensory (Zheng et al, 2001;Li et al, 2004a;Verma et al, 2005;Willis et al, 2005) axons. Moreover, an emerging physiological role for local translation in axons has been described for growth cone guidance and collapse (Zheng et al, 2001;Li et al, 2004a;Verma et al, 2005;Wu et al, 2005).Primary sensory neurons of the dorsal root ganglion (DRG) and trigeminal ganglion (TG) have among the longest axons of the entire neuraxis (greater than one meter for some human DRG neurons). Given the relatively long time interval required for axonal transport of proteins to occur in these neurons following somal synthesis, it would be advantageous if regulable, ondemand protein synthesis would occur at distal sites (for review see: Alvarez et al, 2000;Alvarez, 2001).…”
mentioning
confidence: 99%